Routine immunization experience and practices during the COVID-19 pandemic of caregivers attending a tertiary hospital in Cape Town - Manan, A.; Wessels, T.; Finlayson, H. (Frontiers in Health Services, 2023)
Introduction Immunizations are successful, cost-effective interventions for the control of infectious diseases and preventing mortality. Lockdown restrictions during the COVID-19 pandemic had adverse effects on child-health including access to immunizations. Our study aimed to document immunization status, describe caregiver experiences around accessing immunizations during the COVID-19 pandemic and identify any significant factors associated with immunization status. Methods Caregivers, with children between the ages of 10 to 33 months, attending Tygerberg Hospital Paediatric Department were invited to complete an anonymous survey from 15th September–15th December 2022. Data was captured using a REDCap questionnaire and analysed using Stata Version 17. Results 171 caregivers completed the survey. Immunizations were up to date in 81%. Most (155, 88%) agreed it was important to immunize their child. A third of caregivers (55) felt it was unsafe to attend the clinic and 37% (62) agreed it was difficult to attend. Caregivers receiving a social grant (p = 0.023) or who felt safe attending clinic (p = 0.053) were more likely to be up to date with immunizations. Three-quarters (128, 78%) were aware of recommendations to continue immunization. These caregivers were more likely to think it was important to immunize on time (p = 0.003) and to receive family encouragement (p = 0.001). Caregivers were more likely to attend clinic if they felt it was important to vaccinate on time (p < 0.001) or felt safe attending clinic (p = 0.036). Conclusion Immunization rates were higher than expected but below global targets. Although caregivers feel immunizations are important, unknowns still instilled fear of attending clinics. Social factors such as family support and social grants improve vaccine seeking behaviour.